Empreendedorismo social em ecossistemas de inovação - Silva, Karolina de Melo (2020)
For a long time the third sector was in charge of meeting the needs and alleviating the symptoms of social problems that were not addressed by the State. Under pressure, organizations and private companies incorporated a social and environmental responsibility policy. Until social entrepreneurship opened space for a new conception of the market, contemplating businesses with innovative proposals of social impact that associate profit to their activities, not as an end, but as a means of guaranteeing sustainability and achieving the intended objectives. In Recife, the nucleus of one of the most prosperous innovative ecosystems in the country, impact businesses emerge in a context that sometimes offers them opportunities, sometimes imposes restrictions. Therefore, the following dissertation pursues the objective of identifying the external factors that act in this dynamic and understanding how they constrain or stimulate the development of social impact businesses within this ecosystem. The analysis starts from an extensive theoretical investigation, which presents the main premises of this emerging sector, and from the study of multiple cases. Focusing on the perspective of the social entrepreneur, representatives of four local impact businesses were heard in this research in semi structured interviews, as a way to explore experiences and phenomena in depth. The data collected in the interviews and in secondary sources were contemplated according to the content analysis process presented by Bardin (1977). To answer the problem presented, the elements of the ecosystem that interact in the development of local impact businesses are first identified, based on the theory of ecosystems developed by Spiegel (2017) and Stam (2015). Allied to this perspective, the research is oriented, in a second moment, on formal and informal institutions, to identify the motivating and constraining factors involved in this scenario, based on the studies of North (1990), Urbano, Toledano and Soriano (2010 ), Desa (2012), Moore, Westley and Nicholls (2012) and Robinson (2006). Among the verified limitations are the absence of specific regulations for social impact businesses, the difficult access to investment, ignorance of the social impact business concept and the predominance of conventional market mentality, in addition to the lack of local references and success stories. Among the opportunities, we highlight the articulation of support and development institutions, the incipient involvement of the second sector, the encouragement of innovation and local competence in technology, as well as the visibility of social problems caused by the impacts of the coronavirus pandemic in Brazil.